PENGARUH BAHASA SLANG TERHADAP PROSES KOMUNIKASI MAHASISWA - Nelsa Dwi Mahela; Abdila Abel Mandev; Dhita Amelia; Lili Anggraini; Lupia Ainia Nur; Farel Olva Zuve (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research analyzes the influence of slang language on communication processes and the erosion of character values among students at Universitas Negeri Padang, specifically semesters five to eight. A qualitative descriptive approach involved thirty students through semi-structured interviews, campus observations, and analysis of two thousand four hundred fifty WhatsApp chat transcripts over two months. Results show eighty-seven percent of respondents use slang more than fifty times per day, dominated by